Quantitative Evaluation of Antibiotic Utilization Using the ATC/DDD and DU90% Methods and Length of Hospital Stay Among Pediatric and Adult Pneumonia Patients in Bima - Jihan Istiqomah; Azrifitria; Marvel (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2025)
The primary treatment modality for pneumonia is antibiotic therapy, yet improper use can accelerate bacterial resistance and diminish therapeutic effectiveness. The study aims to evaluate the patterns of antibiotic utilization among hospitalized pediatric and adult patients with pneumonia in a hospital in Bima City, as well as to examine the factors influencing the length of hospital stay during the period of January to August 2020. The evaluation employed the WHO ATC/DDD methodology combined with DU 90% analysis using a descriptive cross-sectional design. Data were obtained retrospectively from medical records, and total sampling. A total of 95 patients met the inclusion criteria, representing all age categories with complete and legible documentation. Quantitative analysis showed that the total antibiotic consumption in pediatric patients reached 39.27 DDD per 100 patient-days, while in adult patients it reached 121.26 DDD per 100 patient-days. Ceftriaxone was the antibiotic with the highest DDD value in pediatric patients and adult patients, with 19.53 and 98.00 DDD/100 patient-days respectively. In the pediatric group, antibiotics within the DU 90 percent segment comprised ceftriaxone, gentamicin, cefotaxime, and azithromycin, whereas in adults, the DU 90 percent segment included ceftriaxone and azithromycin. A total of 97.6 percent of prescriptions were aligned with the hospital formulary. The bivariate analysis indicates that the presence of comorbidities is significantly associated with the length of hospital stay among pneumonia patients (p < 0.05). Meanwhile, patient age and nutritional status did not show a significant association (p > 0.05). Overall, the findings demonstrate a predominance of ceftriaxone use in the management of pneumonia in the hospital. These results highlight the importance of ongoing quantitative surveillance to monitor prescribing trends, and support implementation of antimicrobial stewardship programs to minimize resistance risk and maintain optimal therapeutic outcomes. Keywords: Antibiotic use; Antimicrobial Stewardship Program; ATC/DDD; Ceftriaxone; DU 90%; Pneumonia